Comparison of Analgesic Effects of UST with NSAIDs and without NSAIDs in Patients with De Quervain’s Disease (TAJ: Journal of Teachers Association, 2019)
Background: De Quervain's disease has been described as an entrapment of the extensor pollicis brevis and abductor pollicis longus tendons in the first dorsal compartment of the wrist is a common cause of wrist and hand pain Treatment of the disease consists of pharmacological & non-pharmacological. The non-pharmacological includes immobilization, therapeutic heat and cold, electrical nerve stimulator, thumb stabilizer splint, postural correction at work and the adjustment of tools and equipment. This randomized clinical trial was performed to find out the effects of UST with NSAIDs and without NSAIDs in the patients of De Quervain’s disease.Methods: This randomized clinical trial was performed in the Department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, over a period of six months. Group A-experimental or interventional group and group B-control group by randomization with the help of lottery. Experimental group was managed by activities of daily living (ADLs) instructions, ultrasound therapy (UST) with non-steroidal anti-inflammatory agents (NSAIDs gel), along with thumb spica splint. Control group B received previous management except non-steroidal anti-inflammatory agents (NSAIDs gel). All patients received therapeutic ultrasound in a same dosage (1 watt/ cm 2/min) for 8 minutes. An evaluation was made at initial visit and two weeks interval for 6 weeks. So, there were three follow up visits and these evaluations were performed by the same investigator. In each visit, measurement of pain intensity and disability level were performed by using visual analogue scale (VAS), Tenderness Index and Patient rated wrist evaluation (PRWE) respectively. All results was recorded systematically. A post intervention result was compared with baseline result by SPSS-20Results: Out of 60 total patients 60(100%) had Finkelstein test positive. Significant difference between Group A and Group B was found at week 4 and Week 6 follow up (P0.05). Significant difference between Group A and Group B was found at week 4 and week 6 follow up (P